How virtual reality transforms English classrooms: A systematic literature review - Wan Noor Farah, Wan Shamsuddin; Nik Aloesnita, Nik Mohd Alwi; Umi Kalsom, Masrom (Universiti Malaysia Pahang, 2024)
As a newly emergent technology, virtual reality (VR) is gaining popularity as an assistive tool in language classrooms, leading to a plethora of literature relating to its usage in language classrooms. Therefore, this paper reviews 40 past studies from 2019 to 2023 on utilising VR, specifically in English classrooms, using the systematic literature review as the approach. In contrast to the past research before 2018, most current VR research in English classrooms created their own VR applications. It suggests an increment of VR content for English classes. While these VR applications have different focused language aspects, most focus on vocabulary and speaking tasks. The notion can be attributed to the high engagement of the students and VR’s admirable characteristics, such as its immersiveness and interactivity. The present study also found that the vast majority of the findings reported that the use of VR has positively attributed to learning the target language, which suggests the formidable influence of VR in learning English. Overall, the present study was able to compare contemporary findings on the utilisation of VR in English classrooms, contributing to a more precise and informed knowledge of the area of study.